Post-traumatic arthritis : pathogenesis, diagnosis and management - Olson, Steven A.; Guilak, Farshid (Springer, 2015)
Bringing together the most up-to-date research on post-traumatic arthritis (PTA) and its management, this book is a comprehensive presentation of the current thinking on all aspects of the mechanisms of joint injury and subsequent development of PTA. Divided into thematic sections, it includes discussions of the incidence and burden of PTA, both in society at large and in the military population specifically; the relevant experimental work on PTA, from basic science to animal models; peri-articular tissue responses to of joint injury and potential mechanisms of PTA; the current clinical assessment and treatment of common joint injuries leading to PTA; and emerging technologies and treatments for PTA, including biomarkers and stem cell therapies. Taken together, it will be an invaluable resource for orthopedic surgeons, rheumatologists and other joint injury researchers and clinicians.